PERAN PT.BLOOM AGRO DALAM IMPLEMENTASI PRINSIP FAIR TRADE DI INDONESIA (STUDI KASUS: EKSPOR BERAS ORGANIK PT.BLOOM AGRO KE MANCANEGARA TAHUN 2008-2015) - Munadia Ikhsani; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research describes the role of PT.Bloom Agro to do Fair Teade implementation in Indonesia in the case study is the export of PT.Bloom Agros’s organic rice to foreign country. Fair Trade is the kind of Alternatives trade which populer as donatian movement in 1940. But now in the globalitation era that causes of free trade, fair trade is more popular as alternatives trade movement and as a certification to mark a product has fair tarde guarantee. And in Indonesia PT.Bloom Agro which an exporter company wants to take fair trade to mecanism of their business since it found by a carefull women, Emily susanto because PT.Bloom Agro wants to make farmer’s life better. The research method used was a qualitative with descriptive as a technic of the research. The theories applied in this research are role theory by KJ.Holsty and by Bidle and Bidle to describe about how the role theory. And the perpective used in this research is pluralism perpective by Paul R Viotti and Mark V Kauppi.The conclusion of the research that the role of PT.Bloom Agro to implement fair trade in Indonesia is make coorporation with organics rice farmer in Tasikmalaya, named Gapoktan Simpatik Tasikmalaya, and in Boyolali, named Appoli to get incredible organic rice which planted with System Rice of Intensification(SRI) method and effort to make the organic rice getting fair trade and international organic certificate. And Finally, after getting certified, PT.Bloom Agro succes to export the organic rice to America, Italy, Belgia, Germany, Malaysia, and Singapore.Key words: PT.Bloom Agro, Role, Fair Trade, Certification, Export, Organic Rice.